Actively Open-Minded Thinking and Science Trust: Exploring Croatian Citizens’ Views on Anthropogenic Climate Change and Scientific Consensus on the Issue - Maglić, Marina (24th Psychology Days in Zadar: Book of Selected Proceedings, 2026)
Despite the undeniable scientific consensus regarding the human impact on climate change (CC), research shows that public opinion varies, while digital media abound with information often contradicting scientific findings. In this study, I explore Croatian citizens’ acceptance of anthropogenic CC and their perception of the scientific consensus from the dual-process perspective. Specifically, the primary focus of the study is on the predictive role of actively open-minded thinking (AOT) and science trust as its potential mediator. Additionally, the predictive effects of cognitive reflection and the mediating roles of political and general media trust are explored. Data were collected on a nationally representative sample based on age and gender quotas (N = 1528). The findings reveal that while a majority of citizens accept the reality of anthropogenic CC, many still perceive significant disagreement among scientists on the issue. In the tested structural equation models, AOT emerged as a significant positive predictor of acceptance of anthropogenic CC and a rather weak positive predictor of the scientific consensus on the issue. AOT also positively predicted trust in science and scientists, which partially mediated its effect on acceptance of anthropogenic CC, while there was little evidence for its mediation effect on the perception of scientific consensus. Additionally, media and science trust exhibited positive relationships, while political trust showed a negative relationship with the acceptance of anthropogenic CC. Overall, the findings highlight the importance of a tendency to think with an actively open mind and trust in science and scientists for the acceptance of anthropogenic CC.